Factors associated with overweight and obesity in workers of Piura-Peru: Factores asociados a sobrepeso y obesidad en trabajadores de Piura-Perú - Mejia, Christian R. (2020)
Introduction: Obesity is a public health problem, which also affects the worksector. Objective: Determine the factors associated with overweight and obesity inPiura workers. Methods: A cross-sectional study, using secondary database. Weused the occupational exam records of workers of companies in Sechura – Piura.The main variable was the BMI classification (normal/overweight/obese).Descriptive results and the association between the type of BMI and othervariables were presented. Results: Of the 1203 workers who met the selectioncriteria, 93.2% (1121) were male, and had a median age of 31 (range: 18-63).Significant difference between BMI with respect to waist circumference, hipdiameter, hemoglobin, cholesterol, triglycerides, HDL, LDL and glucose was found.In addition to gender, age and type of test (entrance/periodic/retirement). The studyshowed no significant differences from the place of birth or residence. Conclusions: There were differences in all the physio-anthropometric parametersevaluated with respect to BMI, except birthplace/residence, which shows that therisk of the working population should not be assessed by these demographiccharacteristics. Work programs to improve global health should be generated.